Predicting Rural Industrial Transformation via Coupling Coordination Between Polder-Based Spatial Features and Industrial Development - Wenzhu Zhou; Dawei Wang; Yiwen Zhang; Hanjing Xu (Land)
Rural areas are undergoing a transformation, shifting from traditional agriculture to green and leisure industries, driven by urban–rural imbalances and environmental challenges. This transition, however, presents the growing conflicts between preserving spatial features and promoting industrial development. Based on the unique rural spatial typology of polders, this study integrated theories from cultural, landscape, ecological, economic, and social perspectives to construct a conceptual framework of the interactive relationship between spatial features (SFs) and industrial development (ID). Then, an evaluation index system was constructed to measure the current status of SFs and ID, using data from field surveys, satellite imagery, and 2020 yearbooks, with the Gaochun Polder District, Nanjing (China), as the case study. Next, the coupling coordination degree (CCD) model and a scenario analysis based on orthogonal design were applied to assess the coherence and development between SFs and ID, and to identify strategies for optimizing rural industrial development. The results show that (1) the current SFs and ID are in the break-in and basic coordination stage, with ID lagging behind SFs, and (2) the 25 scenarios generated through orthogonal design were categorized into three groups: high-level coordination with synchronization between the two systems, high-level coordination but ID lagging behind SFs, and basic coordination where ID lags behind SFs. To achieve a high-level coordination with synchronization, specific strategies were proposed to enhance agricultural input–output benefits, improve agricultural scale–quality benefits, and, overall, protect the SF system while making minor adjustments to the village dwelling subsystem. Therefore, the findings provide recommendations for traditional polder villages to optimize their rural industries while preserving the distinctive SFs of the rural cultural landscape.